The effect of 2,4 dichlorophenoxyacetic acid on in vitro callogenesis of cocoa (Theobroma cacao L.) - Sulistyani Pancaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Cocoa (Theobroma cacao L.) development using modern breeding techniques can be facilitated by propagation of planting material through somatic embryogenesis. Various factors that may affect embryogenesis are the composition of culture medium and culture condition. Hormone commonly used to initiate the formation of callus is auxin with type 2.4-D (2.4 Dichlorophenoxy acetic acid). The aim of this study was to determine the effect of the addition of 2.4 -D hormoneson the process of cocoa embryogenesis. The treatments were arragged in factorial combination in completely randomized design, which consisted of two factors. Thefirst factor was the concentration of auxin 2,4-D 25 %, 50 %, 75 %, and 100 %; and the second factor was cocoa clones; Sulawesi 01 and Sulawesi 02. The resultshowed that the addition of 2.4-D hormone up to 100% on somatic embryogenesis of cocoa for Sulawesi 01 clone was not significantly different from Sulawesi 02 clone for all parameters. While on the addition of 2.4-D, there was significant difference between Sulawesi 01 and 02. Cocoa embryogenic callus using the addition of 2.4-D (25%-100%) was significantly different from control. Increased concentrations of 2,4-D hormone which is applied onto media would inhibit the formation of the somatic embryo. Addition of 2.4 D 25%, encouraged towards non-embryogenic callus. Keywords: 2.4 Dichlorophenoxy acetic acid, embryogenic callus, somatic embryos, cocoa, medium culture, hormone